Temperature-dependent folding allows stable dimerization of secretory and virus-associated E proteins of Dengue and Zika viruses in mammalian cells - Slon Campos, J; Marchese, S; Rana, J; Mossenta, M; Poggianella, M; Bestagno, M; Burrone, O (Nature Publishing Group, 2017)
Dengue and Zika are two of the most important human viral pathogens worldwide. In both cases, the envelope glycoprotein E is the main target of the antibody response. Recently, new complex quaternary epitopes were identified which are the consequence of the arrangement of the antiparallel E dimers on the viral surface. Such epitopes can be exploited to develop more efficient cross-neutralizing vaccines. Here we describe a successful covalent stabilization of E dimers from Dengue and Zika viruses in mammalian cells. Folding and dimerization of secretory E was found to be strongly dependent on temperature but independent of PrM co-expression. In addition, we found that, due to the close relationship between flaviviruses, Dengue and Zika viruses E proteins can form heterodimers and assemble into mosaic viral particles. Finally, we present new virus-free analytical platforms to study and screen antibody responses against Dengue and Zika, which allow for differentiation of epitopes restricted to specific domains, dimers and higher order arrangements of E.